PUNISHMENT IMPLEMENTED IN ENGLISH CLASS AT SMA NEGERI 1 NGAGLIK IN ACADEMIC YEAR OF 2014/2015 - Annida Hanifa (PBI 15 UMY 045, 2015)
*45 Punishment is considered as one of the effective methods in managing misbehaviour in the classroom which has become the main problem in educational setting for many years. The research aims to investigate kinds of punishment and students’ perception toward punishment implemented in English class. This research used qualitative research methodology. This research used interview guideline as instrument to collect the data and a cellphone to record the interview. There were four students, two males and two females, who participated in this research. Those students filled informed consents to know their rights as participant of the research. To analyze the data from the interview, this research used open coding, axial coding and selective coding. The result of this research showed that there were several types of punishment implemented in English class at SMA N 1 Ngaglik. The level of punishment implemented in English class varied based on the infringement committed. Besides, this research revealed that the majority of students felt fine when receiving punishment or seeing their friends being punished. The reason was because the disruptive student deserved to be punished. This research also revealed that the disadvantages of punishment implementation in English class were due to the inconsistency of the implementation itself and the level of punishment which was less severe. Another finding of this research indicated that the majority of respondents disagreed with the implementation of physical punishment in the class since it inclined to generate intention to take revenge from students.